Benefits to range resource use and human food supply from multiple species stocking in African livestock systems - Wilson, R.T. (Arab Center for the Studies of Arid Zones and Dry Lands, 1987)
Quantifies some of the benefits to range resource use and human food supply from multiple species stocking in African livestock systems. Gives examples of the use of range resources by camels, cattle, goats and sheep in terms of the percentages of total time spent on feeding. Presents productivity differentials in relation to year and season for different species. Demonstrates the advantages of multiple species herds in drought situations and in post-drought recovery.